Financial Performance Evaluation of Pharmaceutical Companies in Southeast Asia: The Influence of Cash Conversion Cycle, Sales Growth and Firm Size During the COVID-19 Pandemic - Krismonika; Hersugondo, Hersugondo (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
This study investigates the effects of the Cash Conversion Cycle (CCC), sales growth, and firm size on the financial performance of pharmaceutical companies in Southeast Asia during the COVID-19 pandemic (2020–2021). The research focuses on pharmaceutical firms listed in Indonesia, Singapore, and Malaysia, with a total sample of [insert number] companies. Using secondary data collected from Bloomberg, the study employs a quantitative approach and applies multiple linear regression analysis, with Return on Assets (ROA) serving as the indicator of financial performance. The results reveal that CCC has no significant impact on ROA, while sales growth negatively affects ROA, and firm size positively influences ROA. These findings suggest that during periods of global disruption like the pandemic, firm size becomes a key driver of financial resilience, while aggressive sales growth strategies may undermine profitability, possibly due to increased operational risks and supply chain challenges. Although CCC efficiency did not significantly impact profitability in this context, managing firm scale and adapting growth strategies remain crucial for sustaining financial performance during crises. Keywords: Cash Conversion Cycle, Sales Growth, Firm Size, Return on Assets.